2020
DOI: 10.1093/neuonc/noaa232
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastasis detection using machine learning: a systematic review and meta-analysis

Abstract: Background Accurate detection of brain metastasis (BM) is important for cancer patients. We aimed to systematically review the performance and quality of machine-learning-based BM detection on MRI in the relevant literature. Methods A systematic literature search was performed for relevant studies reported before April 27, 2020. We assessed the quality of the studies using modified tailored questionnaires of the Quality Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 48 publications
(77 reference statements)
4
51
0
4
Order By: Relevance
“…In addition, we further performed validations using another temporally separated dataset and data from another institution. Cho et al conducted a systematic review and meta-analysis of 12 studies on BM detection by machine learning ( 46 ). They found that only two studies included consecutive patients and conducted an external validation or temporal separation of test data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we further performed validations using another temporally separated dataset and data from another institution. Cho et al conducted a systematic review and meta-analysis of 12 studies on BM detection by machine learning ( 46 ). They found that only two studies included consecutive patients and conducted an external validation or temporal separation of test data.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR resistant mutations can often be discovered in plasma from NSCLC patients before any clinical symptoms of progression, suggesting that monitoring circulating DNA levels and mutational profiles during the course of the disease could lead to earlier treatment intervention [27,28]. Advanced imaging and radiomics research could potentially represent a non-invasive approach for predicting tumor immunophenotype, but these approaches are still in an early developmental phase [29]. Till date no model has been developed to predict the LCBM immunophenotype based on patient features and treatment details.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a marked transition away from conventional ML programs to deep learning programs, which integrate numerous layers of neural networks akin to human cortical processing, resulting in powerful systems capable of more complex and subtle pattern recognition [ 72 ]. Comparisons in the accuracy of brain metastases detection showed that the deep learning group had a statistically significantly lower rate of false-positives per person when compared with conventional ML, suggesting an ever growing accuracy [ 72 ].…”
Section: Pre-operative Phasementioning
confidence: 99%